Evaluation of a comprehensive, integrated, medical service‐based pharmacy practice model. Issue 1 (7th August 2018) - Vest, Tyler A.; Carrasquillo, Michelle A.; Morbitzer, Kathryn A.; Cruz, Jennifer L.; Eckel, Stephen F.
Abstract : Purpose: Prior to 2008, the pharmacy practice model utilized by the University of North Carolina (UNC) Medical Center was a traditional central pharmacist and clinical specialist model. The department of pharmacy implemented a unique and innovative pharmacy practice model in 2008 organized around medical services. Through this medical service‐based model, all patients are now covered by a pharmacist. The objectives of this study were to evaluate the sustainability of the improvements associated with the medical service‐based pharmacy practice model at UNC Medical Center, which included pharmacist turnover, employee satisfaction and workforce engagement, resident and student involvement in patient care, and inpatient drug costs. Methods: This retrospective analysis focused on data spanning fiscal year (FY) 2004 to 2016. Internal data reporting sources were analyzed to evaluate the outcomes of this practice model. Results: In FY 2016, 67% of work groups were tier 1 (highest satisfaction tier) and 4% were tier 3 (lowest satisfaction tier) and inpatient pharmacist turnover rate was only 7% compared with a 17% hospital turnover rate. Prior to 2008, the average difference between actual and expected drug expenditures was 2.8 million per year, and post‐implementation, the average difference improved to 3.3 million per year. In FY 2017, the department had 35 residents, representing a 169% increase in number of residency positions available compared with FY 2008. In FY 2016, 134 months of early immersion experiences were offered, 29 months of Introductory Pharmacy Practice Experiences (IPPEs), and 417 months of Advanced Pharmacy Practice Experiences (APPEs), which represents a 263% increase in IPPE months and a 369% increase in APPE months from FY 2008. Conclusion: This practice model, along with other factors, has had a continued sustained positive impact on employee engagement, inpatient drug costs, and patient care in our health system. In addition, this practice model is organized around pharmacist responsibilities that support continued growth of pharmacy learners.